EFEKTIVITAS ENDORPHIN MASSAGE TERHADAP TINGKAT KECEMASAN PADA IBU POSTPARTUM SECTIO CESAREAN - Sukmawati, Sukmawati; Lestari, Dian Rosmala (Poltekkes Kemenkes Bandung, 2023)
Anxiety can result in emotional instability, which can cause baby blues. Baby blues causes a lack of interest and interest in the baby. It is characterized by symptoms of the mother being often irritated, blaming herself, crying easily, and having trouble sleeping. Postpartum maternal anxiety can be prevented with several things, such as pharmacological and non-pharmacological therapy. One of the non-pharmacological therapies for dealing with anxiety levels in postpartum mothers is endorphin massage. This research aimed to determine the effectiveness of endorphin massage on anxiety levels in postpartum cesarean section mothers. The type of research is quantitative with a pure experimental research design using a pre-test-post-test experimental design without control group design. The total sample was 100 respondents using the accidental sampling method. Data analysis used the Wilcoxon rank test. This research found that the significance of the p-value was 0.000<0,05, meaning that Ha was accepted and H0 was rejected. So, it can be concluded that there is a difference before and after endorphin massage on the level of anxiety in postpartum cesarean section mothers at the Kendari City Regional Hospital. Midwives are advised to be able to apply non-pharmacological methods to postpartum mothers who experience anxiety, such as endorphin massage, which is very good at reducing anxiety levels.